Nuclear Magnetic Resonance Spectroscopy of Aqueous Plutonium(IV) Desferrioxamine B Complexes. Issue 21 (16th June 2014) - Boggs, Mark A.; Mason, Harris; Arai, Yuji; Powell, Brian A.; Kersting, Annie B.; Zavarin, Mavrik
Abstract: Two aqueous Pu IV ‐desferrioxamine B (DFOB) complexes were characterized by one‐ and two‐dimensional NMR techniques and an unexpected dimeric Pu IV DFOB‐di‐μ‐(O/OH)‐Pu IV DFOB complex was identified. Both "Curie" and "anti‐Curie" behavior were observed for the dimeric species, yet the monomeric species only showed "anti‐Curie" behavior. Diffusion ordered spectroscopy experiments showed an increase in particle size for the two species, which is indicative of a dimeric species. Bond lengths and coordination numbers estimated from X‐ray absorption spectroscopy are consistent with the proposed structures. Abstract : Two aqueous Pu IV ‐desferrioxamine B (DFOB) complexes were characterized by 1D and 2D NMR techniques and a dimeric Pu IV DFOB‐di‐μ‐(O/OH)‐Pu IV DFOB complex was identified. Both "Curie" and "anti‐Curie" behavior were observed for the dimeric species, yet the monomer only showed "anti‐Curie". Bond lengths and coordination numbers estimated from X‐ray spectroscopic analysis support the proposed structures.